Pendidikan Islam di Era Revolusi Industri 4.0 - Nawi Arrasyid Srg, Ja'far; Saputri Pulungan, Melinda; Nasution, Abdusima (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
The Industrial Revolution 4.0 has significantly transformed the education sector, including Islamic education. Digital transformation requires Islamic education to adapt while maintaining Islamic values as the foundation of learning. Islamic education faces challenges such as limited digital competence among educators, unequal technological infrastructure, and curricula that are not yet responsive to digital demands. Therefore, examining Islamic education in this era is essential. This study aims to analyze the role of Islamic education in the Industrial Revolution 4.0, identify challenges and opportunities in digital adaptation, and explore development strategies integrating Islamic values with digital technology. This study employs a literature review method by analyzing relevant national and international journal articles published within the last five years. The findings indicate that Islamic education plays a crucial role in strengthening moral values and character amid rapid technological advancement, while digital integration offers opportunities for adaptive and competitive learning development.